2010
DOI: 10.1029/2008jc005154
|View full text |Cite
|
Sign up to set email alerts
|

Sources of new nitrogen in the Vietnamese upwelling region of the South China Sea

Abstract: In the South China Sea, the southwest monsoon between June and September induces upwelling off the southern central Vietnamese coast. During field campaigns in July 2003 and 2004 we evaluated the importance of nitrate and nitrogen fixation as sources of new nitrogen for phytoplankton primary productivity, both in the actual upwelling zone and in the oligotrophic area farther offshore. Complementary to rate measurements of primary productivity, nitrate uptake, and nitrogen fixation, we determined vertical nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…However, the nitracline depth of the central NSCS during the summer was about 60 m, which was only 10–20 m shallower than that in the KC (Figures a and e). High rates of N 2 ‐fixation with nitracline shallower than 50 m had been observed in the offshore extension zones of the Vietnamese upwelling in the southern South China Sea [ Bombar et al ., ]. Our results suggested that the low diazotroph biomass and nitrogen fixation rate in the central NSCS was caused by its high nitrate fluxes from subsurface (Figure ), which have supplied plenty of nutrients for new production and thus the energy‐costing N 2 ‐fixation became disadvantaged when diazotrophs competing for nutrients with the fast growing nondiazotroph phytoplankton.…”
Section: Resultsmentioning
confidence: 99%
“…However, the nitracline depth of the central NSCS during the summer was about 60 m, which was only 10–20 m shallower than that in the KC (Figures a and e). High rates of N 2 ‐fixation with nitracline shallower than 50 m had been observed in the offshore extension zones of the Vietnamese upwelling in the southern South China Sea [ Bombar et al ., ]. Our results suggested that the low diazotroph biomass and nitrogen fixation rate in the central NSCS was caused by its high nitrate fluxes from subsurface (Figure ), which have supplied plenty of nutrients for new production and thus the energy‐costing N 2 ‐fixation became disadvantaged when diazotrophs competing for nutrients with the fast growing nondiazotroph phytoplankton.…”
Section: Resultsmentioning
confidence: 99%
“…In the framework of VG research cooperation since 2003, seven cruises with different research vessels took place during different seasons. [ Bombar et al , , , Dippner et al , , , Dippner and Loick‐Wilde , , Doan‐Nhu et al , , Loick et al , , Voss et al , ]. The overall objective of these expeditions was the understanding of the nitrogen cycle in an upwelling and river influenced area during monsoon and inter‐monsoon.…”
Section: Observationsmentioning
confidence: 99%
“…It stands out from the SCS sea surface temperature (SST) map in August as a large area with waters 1–2 °C cooler than the surrounding areas (Figure ). The SVU is associated with a high bio‐productivity (Bombar et al, ; Loick et al, ; Lu et al, ; Tang et al, ) and is a major area for the halieutic industry in Vietnam (Levadoux et al, ). It can also cause blooms of haptophyte algae, which are harmful for local coastal ecosystems and aquaculture (Dippner et al, ; Hai et al, ).…”
Section: Introductionmentioning
confidence: 99%